2018
DOI: 10.4103/ijpsym.ijpsym_139_17
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Prevalence of Macrocytosis among the Patients with First Episode of Psychosis and Depression

Abstract: Background: Mood disorders and psychosis has been reported among the patients with macrocytosis; however, its prevalence among the first episode of psychosis and depression is unknown. The purpose of the study was to establish the prevalence of macrocytosis among the patients with the first episode of depression and psychosis. Materials and Methods: In this cross-sectional study, three groups comprising patients with first episode of depression ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…In contrast, depressed participants who experienced increased appetite exhibited marked immunometabolic dysregulation, with higher insulin, insulin resistance, leptin, C -reactive protein (CRP), interleukin 1 receptor antagonist (IL-1RA), and IL-6, and lower ghrelin than subjects in other groups, and the magnitude of their insulin resistance correlated positively with the insula response to food cues [45]. Interesting studies related to depression were reported by Jonas et al [46], Kale et al [47], Behere et al [48], Ransingh et al [49], Mishra et al [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, depressed participants who experienced increased appetite exhibited marked immunometabolic dysregulation, with higher insulin, insulin resistance, leptin, C -reactive protein (CRP), interleukin 1 receptor antagonist (IL-1RA), and IL-6, and lower ghrelin than subjects in other groups, and the magnitude of their insulin resistance correlated positively with the insula response to food cues [45]. Interesting studies related to depression were reported by Jonas et al [46], Kale et al [47], Behere et al [48], Ransingh et al [49], Mishra et al [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an IJPM publication in 2018, examining the prevalence of unrecognized macrocytosis in patients with their first episode of psychosis or depression, bore close similarity to, but did not reference, an earlier IJPM publication which examined the prevalence of Vitamin B12 deficiency in patients presenting with neuropsychiatric symptoms. 7,8 Similarly, an IJPM publication in 2018, examining the prevalence of burnout in Indian psychiatrists, could have cited an earlier IJPM publication which identified compassion fatigue and burnout in Indian clinicians, of whom psychiatrists are a subset. 9,10 The omission of citation of 65%-85% of citation-worthy articles in the IJP and the IJPM is of further concern because the impact factors of journals grow only when articles published in the journals are cited.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on the fact that GABA decreased aggression Antidepressants-They are used because it was found out that serotonin deficiency leads to disturbed circadian rhythm, depression and increase in aggressive behaviour. Patients with dementia often show visible confusion, anxiety, beavourial outbursts, thus the use of antidepressants [17][18][19][20].…”
Section: Gabamentioning
confidence: 99%